Effects of a Stingless Bee Honey Mouth Rinse on Dental Plaque Accumulation: A Randomised Clinical Trial - Misya Humaira Reduan; Nor Suhaira Zulkaflee; Muhammad Annurdin Sabarudin; Nor Haliza Mat Baharin; Nik Madihah Nik Azis; Nur Ayman Abdul Hayei (Springer Science and Business Media LLC, 2026)
Indexed by ERA